1993
DOI: 10.1210/endo.132.2.8425500
|View full text |Cite
|
Sign up to set email alerts
|

Effect of homologous placental lactogens, prolactins, and growth hormones on islet B-cell division and insulin secretion in rat, mouse, and human islets: implication for placental lactogen regulation of islet function during pregnancy.

Abstract: Up-regulation of maternal islet function is essential to accommodate the increased demand for insulin during pregnancy. Previously, we suggested that lactogenic activity regulates islet function during pregnancy. However, this hypothesis was based on the effect of homologous PRLs on islets, since the homologous placental lactogens (or islets) were unavailable. In this study we examine the direct effects of homologous placental lactogens (PL), PRL, and GH on insulin secretion and B-cell division in rat, mouse, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
120
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(129 citation statements)
references
References 39 publications
1
120
0
5
Order By: Relevance
“…The placental lactogens contribute to the development of the mammary glands and to stimulation of progesterone synthesis in the corpora lutea during pregnancy. Recent studies have demonstrated that placental lactogens stimulate insulin secretion and the proliferation of maternal B cells in the pancreatic islets during the latter half of pregnancy in the rat (Brelje et al, 1993;Kawai and Kishi, 1997).…”
Section: The Placenta As An Endocrine Organmentioning
confidence: 99%
“…The placental lactogens contribute to the development of the mammary glands and to stimulation of progesterone synthesis in the corpora lutea during pregnancy. Recent studies have demonstrated that placental lactogens stimulate insulin secretion and the proliferation of maternal B cells in the pancreatic islets during the latter half of pregnancy in the rat (Brelje et al, 1993;Kawai and Kishi, 1997).…”
Section: The Placenta As An Endocrine Organmentioning
confidence: 99%
“…Studies of pancreatic tissue from pregnant women have shown that the most likely source of the increased beta cell mass during pregnancy is neogenesis from unknown progenitor cells as no proliferation of beta cells was seen, whereas the number of small islets was increased . In rodents, it has been shown that somatolactogenic hormones such as prolactin, placental lactogen and placental growth hormone have an important role in the increase in beta cell mass because they are able to stimulate proliferation of beta cells in vitro . A twofold increase in insulin secretion and a fourfold increase in incorporation of 5‐bromo‐2′‐deoxyuridine, an indicator of DNA synthesis during S‐phase, were seen after treatment with rat placental lactogen‐1 and rat prolactin.…”
Section: Introductionmentioning
confidence: 99%
“…Islet cell proliferation was assessed by examining BrdU incorporation as described previously 4 , 14 , 20 , 21 . 10 µM BrdU was added during the last 12 hr of culture.…”
Section: Methodsmentioning
confidence: 99%
“…Glass beads were included in the mounting media (Prolong Gold anti-fade reagent; Life Technologies, Grand Island, NY) to support the coverslips and prevent excessive deformation of the islets. As described previously, 4 , 14 , 20 , 21 the number of BrdU-labeled nuclei/islet was determined by direct observation using a conventional fluorescence microscope. The scattered BrdU-labeled nuclei (typically, 0 to 50) are counted while focusing through intact islets.…”
Section: Methodsmentioning
confidence: 99%